Empire's workshop Latin America, the United States, and the rise of the new imperialism [with a new afterword on the Obama doctrine] - Grandin, Greg, 1962- (Metropolitan Books/Henry Holt and Company, 2010)
The camel not in the Koran -- How Latin America saved the United States from itself -- The most important place in the world: toward a new imperialism -- Going primitive: the violence of the new imperialism -- Bringing it all back home: the politics of the new imperialism -- The third conquest of Latin America: the economics of the new imperialism -- Globalization's showpiece: The failure of the new imperialism -- Iraq is not Arabic for Latin America